2008
DOI: 10.1091/mbc.e07-07-0690
|View full text |Cite
|
Sign up to set email alerts
|

Nebulin Interacts with CapZ and Regulates Thin Filament Architecture within the Z-Disc

Abstract: The barbed ends of actin filaments in striated muscle are anchored within the Z-disc and capped by CapZ; this protein blocks actin polymerization and depolymerization in vitro. The mature lengths of the thin filaments are likely specified by the giant "molecular ruler" nebulin, which spans the length of the thin filament. Here, we report that CapZ specifically interacts with the C terminus of nebulin (modules 160 -164) in blot overlay, solid-phase binding, tryptophan fluorescence, and SPOTs membrane assays. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(124 citation statements)
references
References 52 publications
7
109
2
4
Order By: Relevance
“…The length of the thin filament is an important functional parameter because it determines the degree of overlap between thin and thick filaments, and thereby sets the level of maximum force that a muscle can develop at a given SL. Several recent studies (8,22) have provided experimental evidence to show that nebulin specifies thin filament length via its unique N-and C-terminal sequences. The N-terminal end of nebulin interacts with tropomodulin and the C-terminal end with CapZ, both of which are thought to play a role in specifying the length of F-actin (22,23).…”
Section: Effect Of Nebulin On Maximal Tension Development-we Found Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of the thin filament is an important functional parameter because it determines the degree of overlap between thin and thick filaments, and thereby sets the level of maximum force that a muscle can develop at a given SL. Several recent studies (8,22) have provided experimental evidence to show that nebulin specifies thin filament length via its unique N-and C-terminal sequences. The N-terminal end of nebulin interacts with tropomodulin and the C-terminal end with CapZ, both of which are thought to play a role in specifying the length of F-actin (22,23).…”
Section: Effect Of Nebulin On Maximal Tension Development-we Found Thmentioning
confidence: 99%
“…Several recent studies (8,22) have provided experimental evidence to show that nebulin specifies thin filament length via its unique N-and C-terminal sequences. The N-terminal end of nebulin interacts with tropomodulin and the C-terminal end with CapZ, both of which are thought to play a role in specifying the length of F-actin (22,23). Although details of the mechanism(s) of thin filament length regulation remain to be established (24), that nebulin is a major player in this process is suggested by studies on NEB KO mice (11,12) in which it was found that thin filament length is variable and on average shorter than in WT mice.…”
Section: Effect Of Nebulin On Maximal Tension Development-we Found Thmentioning
confidence: 99%
“…The recently duplicated C-terminal region in the human Nebulin gene, located inside the Z-disc, 27 is involved in binding desmin and is also a region of Nebulin that is known to be involved in different isoforms expressed in different muscle tissue types. 28 Although the location of the alternative splicing sites of nebulin is not known for most of the organisms, our results indicate that some organisms have undergone acquisition of new alternatively spliced exons in the recent past.…”
Section: Expansion Of the C-terminal Region Of Nebulinmentioning
confidence: 99%
“…Within the Z-line, nebulin C-terminal modules interact with the intermediate filament desmin Tonino et al, 2010) as well as the actin barbed-end capping protein CapZ (Pappas et al, 2008). Furthermore, the extreme C-terminal end of nebulin contains a serine-rich region with several predicted phosphorylation sites preceding an Src homology 3 (SH3) domain.…”
Section: Introductionmentioning
confidence: 99%